2017
DOI: 10.1136/bjophthalmol-2017-311136
|View full text |Cite
|
Sign up to set email alerts
|

Topographic correlation between juxtapapillary choroidal thickness and parapapillary deep-layer microvasculature dropout in primary open-angle glaucoma

Abstract: Localised reductions in JPCT were observed at the location of MvD in POAG eyes with parapapillary γ-zone. Such a correlation was not observed in the POAG eyes with only β-zone, but the mean JPCT was significantly smaller in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Therefore, the presence of CMvD may be closely linked to thinner choroid in glaucoma patients, which can result in decreased blood flow to ONH or decreased OPP. 35 Diminished ONH blood flow or OPP may play a significant role in greater severity of glaucomatous damage in OAG eyes with CMvD, given that decreased blood flow to ONH or OPP has been shown to be an independent predictor of glaucoma progression. 36,37 A recent study has found that when CMvD was found in OAG eyes using an OCT-A device, particularly in association with DH, it was significantly associated with progressive RNFL thinning, 5 suggesting that CMvD may have a prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of CMvD may be closely linked to thinner choroid in glaucoma patients, which can result in decreased blood flow to ONH or decreased OPP. 35 Diminished ONH blood flow or OPP may play a significant role in greater severity of glaucomatous damage in OAG eyes with CMvD, given that decreased blood flow to ONH or OPP has been shown to be an independent predictor of glaucoma progression. 36,37 A recent study has found that when CMvD was found in OAG eyes using an OCT-A device, particularly in association with DH, it was significantly associated with progressive RNFL thinning, 5 suggesting that CMvD may have a prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] On the other hand, given that the study subjects were matched by age and VF MD according to the main purpose of this study (i.e., to evaluate CVI according to MvD_P), the generalizability of the current results to the general population of glaucoma patients might be limited. Given that the pathogenic role of the choroidal structure in the pathogenesis of glaucoma is controversial, 3,[26][27][28][29][30][31][32][33] further studies with large numbers of study subjects are required to better elucidate the relationships among the key factors (i.e., glaucoma severity, choroidal thickness, CVI, and MvD_P).…”
Section: Discussionmentioning
confidence: 99%
“…3,5,7,8,12,13 Clinical disc margin was defined as an innermost clinically visible hyperreflective border on both the infrared fundus images and OCT. Both βPPA and γPPA were required to have a temporal width ≥100 μm on at least one radial OCT scan image, as measured by the built-in caliper of Spectralis OCT. 3,5,7,12 According to the circumferential extent of the γPPA, the subjects were divided into three groups: (1) eyes without γPPA (no γPPA group) ( Fig. 1A), (2) eyes with γPPA involving the fovea-BM-opening axis with minimum width at the fovea-BM-opening axis of ≥100 μm (conventional γPPA group; Fig.…”
Section: Analysis Of β-Zone Parapapillary Atrophymentioning
confidence: 99%